Attributes of Moral Leadership: Eight Encounters along the Silk Road (The Macau Ricci Institute Journal, 2019)
The exercise of moral leadership within the Belt and Road Initiative (BRI) is not merely a theoretical study. Rather, the exercise of moral leadership is something that happens, and thus can be described. What would good moral leadership look like? This paper examines the writing of eight personalities along the BRI to identify some of the attributes of moral leadership. The attributes identified here are reciprocity, good governance, transparency, ethical credibility, respect, integrity, humanity, and trust. The eight personalities come from a variety of occupations, and from Asia and Europe. This survey is limited, yet it provides a useful beginning for wider examination.